Tsubaki Stationery Store - Ogawa, Ito, 1973- (Dutton, 2026)
"You always told me that writing is life itself. After many years abroad, Hatoko reluctantly returns to Kamakura to take over the stationery store left to her by her late grandmother. As the custodian of the store, she also inherits the profession of public scribe, a role Hatoko trained for as a child under the guidance of her strict grandmother. As the locals seek out Hatoko's help, she takes on all manner of requests: writing letters of greeting, condolence, farewell, love, and more on behalf of those who come to her. A local community forms around Hatoko and the store, and when the secrets of her late grandmother begin to unravel, Hatoko learns that the role of the scribe requires much more than putting ink to paper. "--